Single-wall carbon nanotube promoted allylic homopolymerization for holographic patterning. (February 2020) - Guo, Jinxin; Cao, Lin; Jian, Jialing; Ma, He; Wang, Dayong; Zhang, Xinping
Abstract: This article interrogates the mechanism for the incorporation of single-wall carbon nanotubes in the photo-initiated thiol-ene polymerization process and its application in holographic patterning. We find that single-wall carbon nanotube is able to turn on the allylic homopolymerization, which is not involved in the conventional thiol-ene photopolymerization process because of the autoinhibition of allyl monomer. This also leads to an enhancement of conversion for both thiol and allyl monomers. For the first time, the ability of single-wall carbon nanotube that promotes an autoinhibition monomer to homopolymerize is revealed. By applying this new mechanism, a flexible single-wall carbon nanotube-polymer composite film for the use of holographic patterning is demonstrated. The effects of the incorporation of single-wall carbon nanotubes on refractive index modulation and mechanical properties of a volume grating recorded are examined. It is shown that a substantial increase in refractive index modulation and diffraction efficiency is realized by small loading of single-wall carbon nanotubes (0.0015 wt%). This validate the proposed mechanisms provide a simple way to control the photopolymerization and therefore to tailor polymers for optical application uses. Graphical abstract: Image 1